2001
DOI: 10.2337/diacare.24.12.2049
|View full text |Cite
|
Sign up to set email alerts
|

Screening Mammogram Utilization in Women With Diabetes

Abstract: OBJECTIVE -To determine whether women with diabetes undergo fewer screening mammograms than matched control subjects.RESEARCH DESIGN AND METHODS -A total of 424 women with diabetes aged 50 -75 years who received their primary care from general internists at a large Midwestern multispecialty group practice were retrospectively studied for frequency of mammography from August 1997 to January 2000. Two control subjects without diabetes (n ϭ 845) were matched to each case by age, sex, provider, and date of visit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 23 publications
7
47
0
Order By: Relevance
“…Two early and one recent case-control studies showed that the rate of having a mammography screening were significantly lower among women with diabetes than among those without diabetes [21][22][23] ; however, these studies were limited either by small sample sizes or the inclusion of women aged ≥50 years. In addition, a Canadian study of women aged 50−67 years also showed a lower rate of receiving a mammography screening among those with diabetes than those without 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Two early and one recent case-control studies showed that the rate of having a mammography screening were significantly lower among women with diabetes than among those without diabetes [21][22][23] ; however, these studies were limited either by small sample sizes or the inclusion of women aged ≥50 years. In addition, a Canadian study of women aged 50−67 years also showed a lower rate of receiving a mammography screening among those with diabetes than those without 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showing comorbidity to be associated with decreased breast and cervical cancer screening did not control for obesity. [27][28][29] From the patient point of view, obese persons may avoid getting CRC screening, particularly colonoscopy and sigmoidoscopy, more than other persons because of embarrassment, concerns about modesty, or fear of pain. In a 1994 study, Olson et al found that obese women commonly delayed or cancelled a physician appointment, including appointments for pelvic exams, because of embarrassment or to avoid being weighed or receiving a lecture about obesity.…”
Section: Discussionmentioning
confidence: 99%
“…First, women with diabetes may have increased screening opportunities due to more frequent physician visits [34], potentially leading to greater breast cancer diagnoses within this population. Second, breast cancer rates tend to be higher among women of higher socioeconomic status (SES) [4], and because diabetes is more prevalent among persons with low SES [35] the association between diabetes and breast cancer may have been underestimated.…”
Section: Introductionmentioning
confidence: 99%